Effect of screw position on load transfer in lumbar pedicle screws: a non-idealized finite element analysis. Issue 2 (25th January 2017) - Newcomb, Anna G. U. S.; Baek, Seungwon; Kelly, Brian P.; Crawford, Neil R.
Abstract: Angled screw insertion has been advocated to enhance fixation strength during posterior spine fixation. Stresses on a pedicle screw and surrounding vertebral bone with different screw angles were studied by finite element analysis during simulated multidirectional loading. Correlations between screw-specific vertebral geometric parameters and stresses were studied. Angulations in both the sagittal and axial planes affected stresses on the cortical and cancellous bones and the screw. Pedicle screws pointing laterally (vs. straight or medially) in the axial plane during superior screw angulation may be advantageous in terms of reducing the risk of both screw loosening and screw breakage.